2018
DOI: 10.3389/fphys.2018.00836
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phospho- and Acetyl Proteomics Analysis of Posttranslational Modifications Regulating Intestine Regeneration in Sea Cucumbers

Abstract: Sea cucumbers exposed to stressful circumstances eviscerate most internal organs, and then regenerate them rapidly under favorable environments. Reversible protein phosphorylation and acetylation are major modifications regulating protein function. Herein, for the first time, we perform quantitative phospho- and acetyl proteomics analyses of intestine regeneration in a sea cucumber species Apostichopus japonicus. We identified 1,862 phosphorylation sites in 1,169 proteins, and 712 acetylation sites in 470 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…After 3 dpe, these processes are also detected in the esophagus remnant [ 74 , 75 , 135 , 136 , 137 ]. An analysis of metabolites and phosphorylation and acetylation processes has shown that a significant rearrangement of cellular metabolism occurs in the holothurian esophagus after 3 dpe [ 135 , 136 ]. As in the activation of the mesenterial coelomic epithelium, it influences the key processes: Transcription, translation, and processing of proteins.…”
Section: Regeneration After Posterior Eviscerationmentioning
confidence: 99%
See 1 more Smart Citation
“…After 3 dpe, these processes are also detected in the esophagus remnant [ 74 , 75 , 135 , 136 , 137 ]. An analysis of metabolites and phosphorylation and acetylation processes has shown that a significant rearrangement of cellular metabolism occurs in the holothurian esophagus after 3 dpe [ 135 , 136 ]. As in the activation of the mesenterial coelomic epithelium, it influences the key processes: Transcription, translation, and processing of proteins.…”
Section: Regeneration After Posterior Eviscerationmentioning
confidence: 99%
“…Almost half of the proteins involved in the amino acid transport and metabolism were upregulated [ 137 ]. It is worth noting here that almost all proteins associated with the “energy production and conversion” term underwent deacetylation [ 136 ]. Thus, the accumulation of energy reserves and their further utilization during regeneration in holothurians is regulated by deacetylation [ 136 ].…”
Section: Regeneration After Posterior Eviscerationmentioning
confidence: 99%
“…Regeneration is a fascinating biological event that has aroused interest in many researchers. For the past two decades, studies have investigated many mechanisms of regenerative processes in sea cucumbers, including morphological features, cell division, dedifferentiation, cell proliferation and migration, nerve regrowth, and molecular regulatory mechanisms (García-Arrarás et al, 1998; Dolmatov and Ginanova, 2009; Sun et al, 2011, 2017a, 2018; Sun L.N. et al, 2013; Li et al, 2017b; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Trypsin/P was specified as the cleavage enzyme, allowing up to two missed cleavages, five modifications per peptide, and five charges. Carbamidomethylation on Cys was specified as a fixed modification, and oxidation on Met, phosphorylation on Ser, Thr, Tyr, and acetylation on the protein N-terminus were specified as variable modifications [49]. False discovery rate thresholds for peptide, protein, and modification site were specified at 5%.…”
Section: Methodsmentioning
confidence: 99%
“…A quantification value was the intensity, and the area was detected for a given quantification channel depending on the setting in the precursor ions quantifier in the consensus method. A t-test with a p -value < 0.05 was applied to distinguish the differential quantitation of acetylated sites [26,49,50]. Fold changes (FCs) >1.2 or <0.83 were also regarded as the criteria of differentially acetylated sites [51].…”
Section: Methodsmentioning
confidence: 99%